2015
DOI: 10.1002/hbm.22789
|View full text |Cite
|
Sign up to set email alerts
|

Differential patterns of functional and structural plasticity within and between inferior frontal gyri support training‐induced improvements in inhibitory control proficiency

Abstract: Ample evidence indicates that inhibitory control (IC), a key executive component referring to the ability to suppress cognitive or motor processes, relies on a right-lateralized fronto-basal brain network. However, whether and how IC can be improved with training and the underlying neuroplastic mechanisms remains largely unresolved. We used functional and structural magnetic resonance imaging to measure the effects of 2 weeks of training with a Go/NoGo task specifically designed to improve frontal top-down IC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
60
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 106 publications
(145 reference statements)
8
60
3
Order By: Relevance
“…However, while a reinforcement of frontal inhibitory mechanisms has been demonstrated following short training with a stop-signal task, only one study found corresponding effects after training with a Go/NoGo task with varying S-R mapping rules (Chavan et al 2015). These authors showed that 2 weeks of such training yielded a decrease in the neural activity within the left and right IFG, as well as changes in both grey and white matter frontal microstructure.…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…However, while a reinforcement of frontal inhibitory mechanisms has been demonstrated following short training with a stop-signal task, only one study found corresponding effects after training with a Go/NoGo task with varying S-R mapping rules (Chavan et al 2015). These authors showed that 2 weeks of such training yielded a decrease in the neural activity within the left and right IFG, as well as changes in both grey and white matter frontal microstructure.…”
Section: Introductionmentioning
confidence: 97%
“…10-15 h in Thorell et al 2009;Johnstone et al 2012;Berkman et al 2014;Chavan et al 2015). For example, training IC with stop-signal tasks (SST) or Go/ NoGo tasks has been found to decrease stop-signal reaction times (SSRT; Guerrieri et al 2012;Manuel et al 2013), or to decrease false alarm rate and/or response time in the trained task, respectively (Schapkin et al 2007;Manuel et al 2010;Johnstone et al 2012;Benikos et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations